Development and study of the functional properties of marshmallow enriched with bee (Apis mellifera) honey and encapsulated probiotics (Lactobacillus rhamnosus) - Colmenares-Cuevas, Saira Itzel; Contreras-Oliva, Adriana; Salinas-Ruiz, Josafhat; Hidalgo-Contreras, Juan Valente; Flores-Andrade, Enrique; García-Ramírez, Edgar Jesús (Frontiers in Nutrition, 2024)
Consumer demand for healthier confectionery products has prompted the confectionery industry to create products that are reduced in sugar content and supplemented with vitamins, antioxidants or biological elements beneficial to health. The aim of this study was to develop marshmallows enriched with Apis mellifera honey and Lactobacillus rhamnosus and to evaluate the effect of honey concentration and gelatin bloom degrees on marshmallow properties. A completely randomized design with a factorial structure was applied with different honey concentrations (0, 50 and 75%) and at different gelatin bloom degrees (265, 300 and 315 bloom degrees); moreover, the physicochemical properties, total phenol content and antioxidant activity of the marshmallow were studied, as well as the viability of the probiotic. The physicochemical properties of the marshmallows were found to be adequate and showed good stability over time. The concentration of honey and gelatin bloom degrees did not significantly affect probiotic viability. The density of the marshmallows decreased as the percentage of honey increased. Additionally, the pH was lower at higher honey concentrations. The marshmallow with 75% honey and 265 bloom degrees had a higher °Brix value. The honey treatments exhibited higher levels of total antioxidant activity and total phenolic compounds than the sugar-only marshmallows. However, the bloom degrees did not have a significant impact on the antioxidant activity and total phenolic compound content. Although the probiotics did not reach the minimum viability needed, their use as paraprobiotics can be considered.